Perspektif Peran Orang Tua dalam Mendampingi Pemuda Berpacaran Sehat di GBT El-Shaddai Bolokan dan GBT Kristus Pembela Balla - Nesya, Bita; Angelina, Claudia (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
This article includes a survey of congregations, especially young people at GBT El-Sahddai Bolokan and GBT Kristus Pembela Balla. This research uses quantitative research methods which aim to explore the perspective of the role of parents in assisting young people in healthy dating at GBT El-Shaddai Bolokan and GBT Kristus Pembela Balla. This quantitative research method was used to collect data through observation and distributing questionnaires to youth in the two churches. This research was conducted to find out whether there is a causal relationship that influences the two variables, namely the perspective of the role of parents (X) in assisting young people in healthy dating (Y). The results of the correlation analysis show that there is a strong and significant relationship between the role of parents and young people's healthy dating behavior with the correlation value between variables X and Y being 0.714 with a significance value of 0.05. It is hoped that the results of this research can make a scientific contribution regarding the perspective of the role of parents in assisting young people in healthy dating.